21st Century Literacy Skills Among Open Distance Learners - Raziana Che Aziz,; Chiam , Chooi Chea; Zulaihan Ismail, (ASEAN Journal of Open and Distance Learning, 2022)
Due to ever changing business environment in the 21st century, employers are demanding a workforce with a different set of skills today. Employers have raised their concerns about the need for a future workforce due to dynamic change in the working place. The workforce needs to be able to handle tough situations which include a well-rounded skills from various areas. Digitalisation is one of the main changes that make the market operation change from physical brick and mortar business to online and virtual business. Skills are needed to be implemented, emphasised and introduced in the education system. Hence, this study aims to study the 21st century literacy skills in open and distance learning (ODL). ODL is a learning that is flexible and conducted online with mainly working adults. This study studies the learning outcomes of a course based on the affective, behavioural and cognitive domains. The results of this study would be able to provide insight to higher education on the improvising the syllabus covered in order to meet the aims of Malaysian 21st Century Learning (Pembelajaran Abad ke-21 (PAK21)). (Abstract by authors)